Global miRNA, lncRNA, and mRNA Transcriptome Profiling of Endometrial Epithelial Cells Reveals Genes Related to Porcine Reproductive Failure Caused by Porcine Reproductive and Respiratory Syndrome Virus - Zhang, Kang; Ge, Lijiang; Dong, Shasha; Liu, Ying; Wang, Dong; Zhou, Chunyan; Ma, Cai; Wang, Yanchao; Su, Feng; Jiang, Yunliang (Frontiers in Immunology, 2019)
Porcine reproductive and respiratory syndrome virus (PRRSV) can cause respiratory disease and reproductive failure in pregnant pigs. Previous transcriptome analyses in susceptive cells have mainly concentrated on pulmonary alveolar macrophages (PAM) and Marc-145 cells, and on the respiratory system. Some studies reported that apoptosis of placental cells and pig endometrial epithelial cells (PECs) is an obvious sign linked to reproductive failure in pregnant sows, but the mechanism is still unknown. In this study, Sn-positive PECs were isolated and apoptosis rates were assessed by flow cytometry. PRRSV-infected PECs exhibited apoptosis, indicative of their susceptibility to PRRSV. Subsequently, the whole transcriptome was compared between mock- and PRRSV-infected PECs and 54 differentially expressed microRNAs (DEmiRNAs), 104 differentially expressed genes (DEGs), 22 differentially expressed lncRNAs (DElncRNAs), and 109 isoforms were obtained, which were mainly enriched in apoptosis, necroptosis, and p53 signal pathways. Integration analysis of DEmiRNA and DEG profiles revealed two microRNAs (ssc-miR-339-5p and ssc-miR-181d-5p) and five genes (SLA-DQB1, THBS1, SLC3A1, ZFP37, and LOC100517161) participating in the apoptosis signal, of which THBS1 and SLC3A1 were mainly linked to the p53 pathway. Integration analysis of DEGs with DElncRNA profiles identified genes involved in apoptosis signal pathway are regulated by LTCONS_00010766 and LTCONS_00045988. Pathway enrichment revealed that the phagosome and p53 pathways are the two main signals causing apoptosis of PECs, and functional analysis revealed a role of miR-339-5p in regulating apoptosis of PECs after PRRSV inoculation.